Prospective epidemiological study on the beginning of varicose veins - Schultz-Ehrenburg, U.; Reich-Schupke, S.; Robak-Pawelczyk, B.; Rudolph, T.; Moll, C.; Weindorf, N.; Hirche, H.; Altmeyer, P.; Stücker, M. (Phlebologie, 2009)
Objective: To conduct a longitudinal vein study in a young study population on when and how varicose veins develop in healthy veins. Population, method: The initial study population consisting of pupils aged 10–12 (BO I, n = 740) underwent clinical and ultrasound follow-up at the ages of 14–16 (BO II, n = 518), 18–20 (BO III, n = 459) and 29–31 (BO IV, n = 136). During BO I-IV all venous findings detected (including preclinical refluxes of the saphenous veins) were recorded. Results: The data were broken down to reveal the incidence and prevalence of venous refluxes (VR), varicose veins (VV) and venous abnormalities (VA) for each part of the study. Furthermore, the data were analyzed longitudinally to identify any correlations between VR and VV in the two saphenous veins. Conclusions: Since none of the study subjects exhibited VV during BO I, the study permits evaluation of the venous situation in the subjects from birth on. The manifestation of a truncal VV is preceded by a VR in the same vein (p = 0.039). VR occurred mainly during puberty (BO I: 2.5%, BO III: 18.5%, BO IV: 25%). A preclinical VR represents a 30% risk (95% CI: 13–53%) of developing a truncal VV within four years, as a consequence, subsequent preventive 2-year follow-up examinations are recommended.
Keywords: Longitudinal vein study; varicogenesis; preclinical saphenous refluxes; risk factor of puberty; CEAP